Influence of Aging on Bioaccumulation and Toxicity of Copper Oxide Nanoparticles and Dissolved Copper in the Sediment-Dwelling Oligochaete Tubifex tubifex: A Long-Term Study Using a Stable Copper Isotope - Thit, Amalie; Sandgaard, Monica Hamann; Sturve, Joachim; Mouneyrac, Catherine; Baun, Anders; Selck, Henriette (Frontiers in Toxicology, 2021)
For engineered metal nanoparticles (NPs), such as copper oxide (CuO) NPs, the sediment is recognized as a major compartment for NP accumulation. Sediment-dwelling organisms such as the worm Tubifex tubifex, will be at particular risk of metal and metal NP exposure. However, a range of complex transformation processes in the sediment affect NP bioavailability and toxicity as the contamination ages. The objective of this study was to examine bioaccumulation and adverse effects of CuO NPs in T. tubifex compared to dissolved Cu (administered as CuCl2) and the influence of aging of spiked sediment. This was done in a 28-day exposure experiment with T. tubifex incubated in clean sediment or freshly spiked sediment with different concentrations of dissolved Cu (up to 230 µg g-1 dw) or CuO NPs (up to 40 µg g-1 dw). The experiment was repeated with the same sediments after it had been aged for 2 years. To obtain a distinct isotopic signature compared to background Cu, both Cu forms were based on the stable isotope 65Cu (>99%). The 28-day exposures to sediment-associated dissolved 65Cu and 65CuO NPs resulted in a clear concentration dependent increase in the T. tubifex 65Cu body burden. However, in spite of the elevated 65Cu body burdens in exposed worms, limited adverse effects were observed in either of the two experiments (e.g., above 80% survival in all treatments, low or no effects on growth rate, feeding-rate, and reproduction). Organisms exposed to aged sediments had lower body burdens of 65Cu compared to organisms exposed to freshly spiked sediments and we suggest that aging decrease bioavailability of both 65Cu forms. In this study, the use of a stable isotope made it possible to use environmentally realistic Cu concentrations and, at the same time, differentiate between newly accumulated 65Cu and background Cu in experimental samples despite the high background Cu concentrations in sediment and T. tubifex tissue. Realistic exposure concentrations and aging of NPs, should preferably be included in future studies to increase environmental realism to accurately predict the environmental risk of metal NPs.